The revolution in science, 1500-1750 - Hall, A. Rupert (Longman, 1983)
Independence movements in Europe, the Americas, and other parts of the world were catalysts for radical economic, social, and cultural reform. And it was during this age of revolutions—an era of rapidly expanding scientific investigation—that profound changes in scientific knowledge and practice also took place.